Teachers as Negotiators of Social Change (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Teachers play a crucial role in shaping society by influencing the minds of young learners. As negotiators of social change, they not only impart academic knowledge but also instill values, foster critical thinking, and promote social justice. This paper explores the multifaceted role of teachers in driving social change, examining their impact on students, communities, and society at large. It highlights the challenges teachers face in this role and suggests strategies to enhance their effectiveness as agents of change.